M13 From interstitial lung disease (ILD) multidisciplinary team meeting (MDT) to anti-fibrotic medication – review of regional MDT referrals. (12th November 2019) - Murphy, CJ; Donaldson, C; Langlands, L; Wiscombe, S; Simpson, AJ; Forrest, IA
Abstract : Introduction: NICE guidelines recommend diagnosis of idiopathic pulmonary fibrosis (IPF) only with the consensus of an MDT. 1 Patients with (suspected) ILD in the North East are referred from 12 regional trusts to the Newcastle Interstitial Lung Diseases Service (NILDS) MDT for discussion. NILDS is the regional prescriber for anti-fibrotic medications (AFM) Nintedanib and Pirfenidone. Aims: To review the referrals made to the NILDS MDT, establish the number of patients diagnosed with IPF and those prescribed AFM at first follow up. Method: Retrospective review of all NILDS MDT patient lists over a twelve month period (January – December 2016) and review of MDT and subsequent clinic follow-up outcomes. Results: 659 patients were referred to the MDT. In 43 (6.5%) cases no records or minimal information could be found, leaving 616 patients for analysis. New patients referred into the NILDS who were diagnosed with IPF at the MDT (n=118) were seen within 9.1 weeks of the MDT taking place (range: -1 day – 34.7 weeks). In total (NILDS and non-NILDS patients), 199 (32.3%) patients were diagnosed with IPF or included IPF in the differential diagnosis. 72/199 (36.2%) patients were started on AFM at the first outpatient appointment following the MDT – 48/72 (66.7%) on Nintedanib and 24/72 (33.3%) on Pirfenidone. 127/199 (63.8%) patients did not receive AFM. Reasons for not prescribing AFM (see table 1) were multiple in nature for 8 patients. This review did not include patients receiving AFM at later stages in their follow-up period or those discussed at MDTs prior to 2016. Conclusion: Promising results were shown for mortality, PFS and lung function for patients on antifibrotics, although this data may favour commencement of nintedanib as first line therapy, given the lower rates of treatment discontinuation by 3 months. Patients who were able to tolerate antifibrotic therapy for the first 3 months were shown to have a significantly improved mortality.